2015
DOI: 10.1039/c4ra14542a
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and electrochemical properties of rare earth (Gd, Nd) doped V2O5 nanostructures synthesized by a non-aqueous sol–gel route

Abstract: Vanadium pentoxide nanostructures have been obtained from an alkoxide sol–gel, prepared by a simple and inexpensive facile non-aqueous method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…The prepared samples presented a typical vanadium pentoxide optical absorption spectrum ( Figure 5 a), extending almost to 600 nm, in good agreement with the literature [ 14 , 15 , 35 ].…”
Section: Resultssupporting
confidence: 88%
“…The prepared samples presented a typical vanadium pentoxide optical absorption spectrum ( Figure 5 a), extending almost to 600 nm, in good agreement with the literature [ 14 , 15 , 35 ].…”
Section: Resultssupporting
confidence: 88%
“…The O1s peak indicates the presence of oxygen in V‐CP. The peaks located at 530.0 and 532.6 eV are attributed to the oxygen atom coordinated with vanadium (O—V) and carbon (O—C) in the V‐CP specimen, respectively . Further characterizations of the V‐CP sample are given in the Supporting Information (SI) (Figure S1a–c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in V 4+ concentration played a significant role in decreasing the electronic conductivity and Li-ion transport and thus limiting the electrochemical performance for 3%Al 3+ -V2O5. Experimentally, this was observed with low capacities in the C-rate test, large redox peak separations in the CV and in the impedance results with a decreased Rct implying increased oxygen vacancies [28,29]. aluminium nitrate and poly(vinylpyrrolidone) followed by heat treatment at 400 °C [22].…”
Section: Overall Discussionmentioning
confidence: 99%
“…Coustier et al found that doping V2O5 xerogels with Ag + increased conductivity, which was partially due to an increase in V 4+ sites and the associated increase in polaron hopping [25,26]. Higher electronic conductivities were attributed to the presence of V 4+ in a range of other doped V2O5 compounds: (i) Cr 3+ doped V2O5 at both 2 and 5 at% loadings [27], (ii) 2 at% Cu 2+ doped V2O5 [28], and (iii) 3 at% loading for Gd 3+ or Nd 3+ doped V2O5 [29]. Furthermore, whilst the exact dopant level was not specified in terms of a molar ratio, a similar observation was made for Fe 3+ doped V2O5 with three different loadings [30].…”
Section: Introductionmentioning
confidence: 97%